PERSPEKTIF AKUNTANSJ ATAS ASET PENGETAHUAN (KNOWLEDGE ASSET) - Widyaningdyah, Agnes Utari (Jurnal Akuntansi Kontemporer, 2009)
Today s economies shifted the dynamic business environment into information age where people interact with knowledge. In this new economy, knowledge management and intellectual capital are emerging as the p"imary source of wealth. Some companies in Europe have already implemented various knowledge measurement techniques and provide it in particular report called knowledge and intellectual capital report. However, all of those techniques and reports have limitations and many suffer ji-om a lack of practical testing. They need to standardize in order to give a better perception for the participant of the organizations. This popel' discusses at the nature of knowledge, proposed alternative methods of knowledge accounting and the prospects and possibilities for knowledge accounting.